THE IMPACT OF SMARTPHONE ADDICTION ON CHILDREN IN MEDAN - Nasution, Mawaddah (Proceeding International Seminar of Islamic Studies, 2024)
This is qualitative research with a phenomenological approach. The subjects were young children aged 5–6 in Medan City who were indicated to be addicted to smartphones for 3–4 hours a day. Data collection is done using observation techniques and interviews with children, and data triangulation is done with parents to verify the accuracy of the data obtained. The results of this study show that the impact of smartphone users on children is divided into physical, psychological, consisting of positive and negative, as well as social. Physically, children experience eye fatigue and dizziness. Psychically, they experience increased emotional and less responsiveness to the environment, anger, irritability, and tantrums, while on the positive side, they can learn the concepts of numbers and letters, have a new vocabulary, have active communication skills, know the short suras in the Qur'an, and have greater curiosity for something. And socially, children are becoming more often at home playing smartphones.